Effectiveness of an instructional design in the academic performance of students of an online course - Quiroz Campas, Celia Yaneth; Armenta Zazueta, Lizeth; Hinojosa Rodriguez, Carlos Jesús (Unidad Editorial UPTC, 2020)
The purpose of this research was to elaborate an online instructional design, and to identify the effectiveness of the academic performance on a course of the educational program bachelor’s in administration of a University of northern Mexico. The course was taught in “SAETI, Sistema de apoyo a la educación con tecnologías de internet” (Support System to education with Information Technologies). The instructional design of the course was tested on this platform with students of fourth and fifth semester. This research was done under a quasi-experimental focus with a quantitative approach. Once the online instructional design was developed, an evaluation instrument was applied to measure the effectiveness of the use and application of an online instructional design. The student sample to be selected was made with two natural class groups, one control and one experimental group. In addition, three research questions were answered, the first question refers to the differences in the academic performance of students in an online course, when an instructional design is used. According to the results it is verified that there are significant differences in the experimental group, where an online instructional design was used, and it is demonstrated with the result of the t-student test. For the second research question, the advantages for the student are presented, the effectiveness of the application of an instructional design in the activities of an online course and the third research question investigated what the advantages for the teacher in the use of an instructional design in an online course are; the findings of this research showed that the instructional design used in the two units of competence was effective. Keywords: instructional design, academic performance, instructional design models, learning theories Code JEL: I20, I21, I23 Received: 24/06/2019. Accepted: 12/02/2020.  Published: 27/04/2020